Child protection: managing conflict, hostility and aggression - Laird, Siobhan E. (Policy Press, 2013)
As they intervene in families to reduce the risk of harm to children, child protection social workers around the world are confronting increasingly high levels of hostility and aggression from some parents. Investigations into the deaths of children known to social services have accused social workers of failing to use their professional authority to challenge parents. This much needed book analyses public inquiries and serious case reviews to reveal the dynamics of hostility and aggression which contribute to the failure to protect children. These can occur within the office environment and between social workers and parents or their partners. The book details applied theories of aggression in conjunction with the skills required for dealing with anger, conflict and aggression. A set of tools and reflective exercises assists the application of theory to day-to-day child protection practice. This indispensable and practical text is ideal for social work students, practitioners, trainers and academics specialising in child protection.